Vision of Science Education in National Education Policy-2020 - Singhal, Mamta; Wadhwa, Manisha (Voices of Teachers and Teacher Educators, 2022)
Science and technology have profound impact on our lives. The advancements in the various fields of science such as telecommunication, medicine, agriculture and energy on one hand have made our lives easy but at the same time have resulted in environmental degradation and other concerns related to health and mental well-being. Our education system has a crucial role to play in understanding and addressing these concerns right from the beginning of school education. It is well understood and emphasised in several policy documents that all citizens should develop a scientific temperament, possess basic process skills and knowledge of scientific concepts in order to make informed and meaningful choices in the situations concerning science, technology and society. This ability is also called scientific literacy. National Education Policy (NEP) 2020 has envisaged bringing major educational reforms to achieve the Sustainable Development Goals (SDGs) of Agenda 2030. This paper discusses the vision of NEP 2020 with respect to science education in schools and how our education system can possibly contribute towards making scientifically literate citizens and achieving the SDGs of Agenda 2030.